Cultural heritage safeguarding through social entrepreneurship: a case study analysis in George Town UNESCO World heritage site, Malaysia - Joey Law; Jeen Wei Ong; Kamarulzaman Ab. Aziz (Cogent Business & Management, 2024)
This article suggests social entrepreneurship, driven by the focal point of Social Entrepreneurship Orientation, as a mechanism to safeguard the cultural heritage of George Town, a UNESCO World Heritage Site, through the case study of two entities - a legally registered organisation (ORG01) and an informal group (ORG02). Given the complex mechanism of social entrepreneurship, this study employed a qualitative approach utilising the Theory of Change framework to dissect the intricated aspects of social entrepreneurship initiatives into processes and challenges, focusing on inputs, activities, outputs, outcomes, and impacts. The key findings shed light on the roles of two entities embodying the characteristics of Social Entrepreneurship Orientation in their safeguarding efforts. Lastly, this article contributes to a practical understanding and possible development of a sustainable model for cultural heritage safeguarding by comprehending the social entrepreneurship process and aligning with Sustainable Development Goal 11 of fostering sustainable cities and communities.
Keywords: 650; Social entrepreneurship initiatives; sustainability initiatives; theory of change; cultural heritage safeguarding; urban heritage conservation; SDG alignment